A long term perspective on the euro - Bordo, Michael D.; Harold, James; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2008)
This essay will evaluate the experience of the first decade of EMU and the euro in historical perspective. It will ground the establishment of EMU and the euro in the context of the history of international monetary cooperation and of monetary unions. A discussion of the origins, key operating characteristics and problems encountered by earlier monetary arrangements will serve as a backdrop for an evaluation of the euro's performance and challenges in future decades. The essay will develop and expand upon the following three themes: 1. Lessons from the evolution of past monetary unions for EMU; 2. Fiscal policy arrangements for EMU in historical perspective; 3. Challenges facing EMU. The first two take an historical perspective. The third looks to the future.
Economic Papers